Climate Signals in the Black Sea From a Multidecadal Eddy-Resolving Reanalysis - Lima, Leonardo; Ciliberti, Stefania Angela; Aydoğdu, Ali; Masina, Simona; Escudier, Romain; Cipollone, Andrea; Azevedo, Diana; Causio, Salvatore; Peneva, Elisaveta; Lecci, Rita; Clementi, Emanuela; Jansen, Eric; et al. (Frontiers in Marine Science, 2021)
Ocean reanalyses are becoming increasingly important to reconstruct and provide an overview of the ocean state from the past to the present-day. In this paper, we present a Black Sea reanalysis covering the whole satellite altimetry era. In the scope of the Copernicus Marine Environment Monitoring Service, the Black Sea reanalysis system is produced using an advanced variational data assimilation method to combine the best available observations with a state-of-the-art ocean general circulation model. The hydrodynamical model is based on Nucleus for European Modeling of the Ocean, implemented for the Black Sea domain with a horizontal resolution of 1/27° x 1/36°, and 31 unevenly distributed vertical levels. The model is forced by the ECMWF ERA5 atmospheric reanalysis and climatological precipitation, whereas the sea surface temperature is relaxed to daily objective analysis fields. The model is online coupled to OceanVar, a 3D-Var ocean data assimilation scheme, to assimilate sea level anomaly along-track observations and in situ vertical profiles of temperature and salinity. Temperature fields present a continuous warming in the layer between 25-150 m, where the Black Sea Cold Intermediate Layer resides. This is an important signal of the Black Sea response to climate change. Sea surface temperature shows a basin-wide positive bias and the root mean square difference can reach 0.75 ºC along the Turkish coast in summer. The overall surface dynamic topography is well reproduced as well as the reanalysis can represent the main Black Sea circulation such as the Rim Current and the quasi-permanent anticyclonic Sevastopol and Batumi eddies. The system produces very accurate estimates of temperature, salinity and sea level which makes it suitable for understanding the BS physical state in the last decades. Nevertheless, in order to improve the quality of the Black Sea reanalysis, new developments in ocean modelling and data assimilation are still important, and sustaining the Black Sea ocean observing system is crucial.